Environmental law - Bell, Stuart , 1965-; McGillivray, Donald , 1967-; Pedersen, Ole W. (Oxford University Press, 2013)
This edition includes material on environmentalism and the law, international environmental law, access to environmental justice, noise pollution and new legislation on pollution prevention and new case law